Simple blue almost hermetic: Reading and cognition in Pablo Neruda’s "Oda a Federico García Lorca" - López Carballo, Pablo (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
The verse “porque por ti pintan de azul los hospitales” of the poem «Oda a Federico García Lorca», by Pablo Neruda, presents several interpretive enigmas, which go beyond the symbolic. In this paper we intend to investigate the reading possibilities from the teachings that cognitive poetics offers us. To do this, we will integrate various points of view into the analysis to help us better understand its scope and survival.